2006
DOI: 10.1523/jneurosci.2964-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous NMDA-Dependent Long-Term Potentiation of EPSCs and Long-Term Depression of IPSCs in Cultured Rat Hippocampal Neurons

Abstract: A fundamental issue in understanding activity-dependent long-term plasticity of neuronal networks is the interplay between excitatory and inhibitory synaptic drives in the network. Using dual whole-cell recordings in cultured hippocampal neurons, we examined synaptic changes occurring as a result of a transient activation of NMDA receptors in the network. This enhanced transient activation led to a long-lasting increase in synchrony of spontaneous activity of neurons in the network. Simultaneous long-term pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 67 publications
(81 reference statements)
1
18
0
Order By: Relevance
“…Previous reports have identified that LTP-inducing stimuli at glutamatergic synapses in the hippocampus can simultaneously potentiate excitatory and depress inhibitory transmission (Chevaleyre and Castillo, 2003;Ivenshitz and Segal, 2006). To our knowledge, however, there is no evidence of glutamatergic stimuli that concurrently depress excitatory transmission and enhance inhibition.…”
Section: Discussionmentioning
confidence: 83%
“…Previous reports have identified that LTP-inducing stimuli at glutamatergic synapses in the hippocampus can simultaneously potentiate excitatory and depress inhibitory transmission (Chevaleyre and Castillo, 2003;Ivenshitz and Segal, 2006). To our knowledge, however, there is no evidence of glutamatergic stimuli that concurrently depress excitatory transmission and enhance inhibition.…”
Section: Discussionmentioning
confidence: 83%
“…Although it is not associated with a specific class of spines (stubby, mushroom, long), SP is more prevalent in spines with a large head that are innervated by synaptophysin-containing terminals. The presence of SP in spines correlates with the presence and efficacy of functional GluRs of the AMPA type, but not of the NMDA type and its presence is upregulated by a transient activation of the NMDA-R that causes a long lasting potentiation of synaptic connectivity (Ivenshitz and Segal, 2006). SP has been associated with the spine apparatus, a membranous extension of the dendritic smooth endoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%
“…A transient (5 min) intense activation of synaptic NMDA-R has been reported to produce a long-lasting increase in excitatory postsynaptic current magnitudes recorded between pairs of neurons in culture (Ivenshitz and Segal, 2006) and to enhance the delivery of GluR1-clusters into dendritic spine heads (Korkotian and Segal, 2007). We examined the effect of chemical LTP (cLTP) on SP puncta in dendritic spine heads using immunostaining for endogenous SP in GFP-transfected cells (Fig.…”
Section: Transient Activation Of Nmda-r Regulates Formation Of Synaptmentioning
confidence: 99%
“…It has been previously shown that GABA Breceptors mediate inhibition of synaptic release through modulation of presynaptic Ca 2ϩ channels Carter 2010, 2011;Marshall 2008;Otmakhova and Lisman 2004;Tang and Hasslemo 1994). In particular, activity-induced GABA B -dependent plasticity was attributed to activation of presynaptic receptors of inhibitory neurons (Ivenshitz and Segal 2006). According to this scenario, the first stimulus in a paired-pulse protocol causes a GABA transient that reduces release during the second pulse, through a di-synaptic mechanism.…”
Section: Apparent Discrepancy With Learning-induced Reduction In Pairmentioning
confidence: 99%